The Leader’s Roles in Non-Profit, For-Profit and Public Organizations: The Case of Poland - Hanna BORTNOWSKA; Bartosz SEILER (Communications of International Proceedings, 2020)
Leadership in organizations is one of the most important subjects analysed in contemporary management literature. This paper focuses on the roles of leaders that they can play in different types of organisations. The purpose of the article is to answer the following research question: Are there any differences between nonprofit, for-profit and public organizations regarding the performance of the leader’s roles? To that end, a cross-sectoral survey was conducted in 2019 among 105 leaders and 210 non-leaders (the sampling was non-random). The statistical analysis showed that there are no fundamental differences in leaders’ roles in nonprofits, for-profits and public organizations. In all three, the most important roles were those of a: working leader, trusted leader, strategic leader, and supportive leader.
Keywords: Leader's Roles; Nonprofit Organizations; For-profit Organizations; Public Organizations.